Avaliação do comportamento da retrorrefletividade em rodovia com micro revestimento asfáltico à frio - Renz, Eduardo Martins (2018)
More than one million people are killed annually around the world as a result of traffic accidents. In Brazil, this epidemic costs the public coffers 56 billion a year. More than half of the fatal accidents in Rio Grande do Sul occur in night or dawn periods, but less than a third of the displacements occur at these times. Considering these affirmatives, road safety devices operating in periods with no sunlight should be effective in order to provide safety to road users. The main devices acting in these periods are road demarcations and retroreflective signs. Therefore, the objective of this research is to follow the retroreflective indices of the road demarcations applied on a section of BR-287, located in the city of Santa Maria - RS. The surface of the pavement is equipped with MRAF. The work consisted in the monitoring of retroreflectivity and surface texture of the stretch during two years. The results showed that these demarcations applied on this type of surface tend to have lower retroreflectivity values than the others, but with the same degradation rate, 0.01% per day. The retroreflectivity values tend to fall more rapidly in the first days of life, presenting a peak near the 30 days and, after that, fall again smoothly until they present a horizontal asymptote. No influence of the precipitation on the retroreflectivity values was found in this study, since in the study section there was little request of the lines in front of the friction with the vehicle tires. The measurement direction does not interfere in the results of retroreflectivity in places where the paint speed was low. The white demarcations present, on average, 30% higher retroreflectivity values compared to the yellow demarcations. The demarcations showed 50% lower retroreflectivity values when measured with geometry equipment equal to 30m when compared to values measured with 15m geometry. When wet, demarcations lose about 80% of their retroreflective capacity. The periodic cleaning of the demarcations was beneficial for the retroreflectivity indices. It was evidenced that the macrotexture of the pavement is directly connected with the retroreflectivity of the demarcations, flatter classes have higher retroreflectivity values. The microtexture of the demarcations also had an influence on the retroreflective properties. In addition, the study determined the optimal rate of application of glass microspheres 325g / m² painted, different from what is today in SICRO 250g / m².